2021
DOI: 10.3389/fmed.2021.618757
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Sputum Torque Teno Virus Load and Lung Function and Disease Severity in Patients With Chronic Obstructive Pulmonary Disease

Abstract: Purpose: Viral load of Torque Teno virus (TTV) is elevated in immunosuppressed patients. The weakened immune response is typical in chronic obstructive pulmonary disease (COPD) patients. However, the relationship between TTV and COPD is still unknown.Patients and Methods: We enrolled 91 patients admitted to hospitals with acute exacerbation of COPD (AECOPD) between January 2017 and August 2017 (ClinicalTrials.gov ID, NCT03236480). Sputum samples were gathered during hospitalization and the 120-day follow-up. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
0
10
0
2
Order By: Relevance
“…58,59 Frye et al observed an unexpectedly high baseline rate of TTV-negative patients in their LuT cohort (67.6%), which was explained on the grounds of differences in PCR sensitivity. 60 To put these figures in context, the presence of detectable TTV viremia in non-transplant patients with chronic conditions leading to end-stage organ failure is estimated at 41.7% 46 to 80% 47 for those on hemodialysis, 95% for those with chronic obstructive pulmonary disease, 61,62 and as high as 100% for those with idiopathic pulmonary fibrosis. 63,64 Of note, these figures are higher as compared to healthy individuals, 32,65 supporting the hypothesis that TTV replication is enhanced not only by impaired immune competence but also by persistent low-grade inflammatory status.…”
Section: Baseline Prevalence and Post-transplant Kineticsmentioning
confidence: 99%
“…58,59 Frye et al observed an unexpectedly high baseline rate of TTV-negative patients in their LuT cohort (67.6%), which was explained on the grounds of differences in PCR sensitivity. 60 To put these figures in context, the presence of detectable TTV viremia in non-transplant patients with chronic conditions leading to end-stage organ failure is estimated at 41.7% 46 to 80% 47 for those on hemodialysis, 95% for those with chronic obstructive pulmonary disease, 61,62 and as high as 100% for those with idiopathic pulmonary fibrosis. 63,64 Of note, these figures are higher as compared to healthy individuals, 32,65 supporting the hypothesis that TTV replication is enhanced not only by impaired immune competence but also by persistent low-grade inflammatory status.…”
Section: Baseline Prevalence and Post-transplant Kineticsmentioning
confidence: 99%
“…However, the presence and the high load of TTV have been associated with some acute respiratory diseases both in children and in adults [ 27 , 88 ]. In adults, Xie et al [ 89 ] showed a high prevalence of distribution of torque teno virus (95.6%) in the lungs of 91 patients with COPD, revealing that the observation rate of TTV in COPD is higher than that of other chronic respiratory diseases. Interestingly, the authors stated that an alteration of the immune system in COPD patients could contribute to the high prevalence of TTV, reflecting the immunocompetence of hosts [ 88 , 89 ].…”
Section: Anelloviruses and Chronic Respiratory Diseasesmentioning
confidence: 99%
“…More recently, in adult patients with coronavirus disease 2019 (COVID-19), the respiratory microbiome was investigated to detect potential changes in the bacterial communities and commensal viruses, such as AVs and redondoviruses, in association with this pathological condition [ 89 , 90 ]; specifically, the authors collected 507 oropharyngeal, nasopharyngeal, and endotracheal samples from 83 hospitalized COVID-19 patients and 75 samples from 13 critically ill patients hospitalized for other diseases, showing an interesting dysbiosis of the lung microbiome in hospitalized patients with COVID-19 compared to other patients. Noteworthy, the authors found that AVs and redondoviruses resulted in being important factors to distinguish patients that were intubated or not [ 89 , 90 ].…”
Section: Anelloviruses and Chronic Respiratory Diseasesmentioning
confidence: 99%
See 2 more Smart Citations